1995
DOI: 10.1177/107110079501600707
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the Achilles Tendon and Plantar Fascia in Relation to the Calcaneus in Various Age Groups

Abstract: Ten adult cadaver feet, three neonatal feet, and the feet of two fetuses were dissected to investigate whether an anatomical continuity exists between the fibers of the Achilles tendon and the plantar fascia. Histologic sections of the feet were done in three age groups: neonate, persons in their mid-20s, and the elderly. As the foot ages, there appears to be continued diminution of the number of fibers connecting the Achilles tendon and plantar fascia. The neonate has a thick continuation of fibers, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 10 publications
2
76
0
2
Order By: Relevance
“…The occurrence and insertional variety of the plantaris tendon are similar to those reported [9]. Anatomic reports of this area exclusively involved gross anatomic [7,34] or sagittal sections [32,41]. Observations performed only in one plane, however, may not reflect the Achilles tendons three-dimensional insertions.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The occurrence and insertional variety of the plantaris tendon are similar to those reported [9]. Anatomic reports of this area exclusively involved gross anatomic [7,34] or sagittal sections [32,41]. Observations performed only in one plane, however, may not reflect the Achilles tendons three-dimensional insertions.…”
Section: Discussionsupporting
confidence: 57%
“…However, when the Achilles tendon also is illustrated, confusion is caused by presenting different insertional tendon shapes. Some anatomic [1,29] and operative [5,42] textbooks and articles [7,32,34,41] have depicted the Achilles tendon insertion only from a lateral or medial view leading to the impression that the tendon's shape does not change from its oval midportion cross section to the insertional area [5,7,9,29,42,44]. Images of the Achilles tendon insertion in a transverse plane occasionally are presented, showing a slightly bent [19,27,35] or an unbowed [8] Achilles tendon insertion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the plantar fascia contributes to a more homogeneous distribution of Achilles stress and permits transmission of force from the hind to the forefoot and vice versa. Snow et al (1995) have demonstrated that aging produces a continued diminution of the number of fibres connecting the Achilles tendon and the plantar fascia. The neonate has a thick continuation of fibres, the middle aged foot has only superficial periosteal fibres that continue from tendon to fascia, while in elderly feet no connections could be found at all.…”
Section: Medial Portionmentioning
confidence: 98%
“…Las tendinosis son procesos degenerativos cr贸-nicos asociados al sobreuso [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Un tend贸n sano contiene un 95% de tenocitos y tenoblastos, que pose茅n hasta un 80% de col谩geno tipo I y un 2% de elastina 15 .…”
Section: Introductionunclassified